Forming of positive image of Ukraine as a tool for its investment attractiveness rise - Liudmyla Shabalina; Nataliia Kiskina (Cхід, 2013)
Differences and correlations between the terms of territory image, brand and positioning are revealed in the article. Image ofUkraineis analyzed based on the rating assessment of the leading world agencies and organizations. Assessment of the investment attractiveness of Ukraine based on European Business Association gives evidence that investment attractiveness integral index fell by 60 % in the first quarter of 2013 cjmpared to 2011.